Beyond the battlefield: the political economy of armed conflict and peace in Colombia - Dodd, Oliver (2025)
The Colombian armed conflict, formally beginning in 1964, resulted in a historic peace agreement in 2016 between the government and the Fuerzas Armadas Revolucionarias de Colombia (FARC). Despite the significance of this milestone after 52 years of war, the conflict’s origins, development, and path to peace have only been partially addressed. The Colombian case is not only remarkable for its duration but also for how it developed. The conflict evolved from a highly localised rural conflict in the 1960s to a national and regional phenomenon by the 1990s before experiencing a notable decline in the post-2000 period, culminating in the 2016 peace agreement. Prevailing theories discussing the conflict’s origins, escalation and turn to peace tend to reduce the dynamics to simplistic explanations, especially by highlighting immediate agent motivations, state weaknesses, drug trafficking, and the changing balance of power on the battlefield. In contrast, this thesis goes beyond the battlefield, analysing how broader political-economic conditions underpinned the conflict’s origins, escalation, and decline. It examines conflict and peace-making from a critical international political economy perspective, situating the agency and strategies of key social forces against the background of the Colombian form of state’s integration within a changing context of global capitalism and world order. This connects immediate agent motivations and strategies with the underlying dynamics of the international political economy. By uncovering and comparing the intersection of local, national and international political-economic factors shaping the distinct problems of conflict onset, escalation, and decline, the thesis offers insights into the nature of the international political economy and the challenges of addressing protracted armed conflicts in the Global South. In doing so, the thesis draws from a broad range of primary sources, including interviews with politicians, business and labour leaders, former insurgents, retired military and police commanders, NGO representatives, and secondary material published in Colombia. These sources are combined with extensive archival material, including military, police, and intelligence documents, guerrilla communiqués, correspondence and reports, as well as newspapers and magazines. The thesis contributes to debates on political violence, (counter)insurgency, and conflict resolution by highlighting how international political-economic change is central to shaping the contrasting outcomes of war and peace. The project, therefore, provides original research and new inter-disciplinary insights for both scholars and practitioners while challenging conventional agent-based and state-centric explanations.